Protestant sects of Kharkiv province under the conditions of freedom of conscience (1905–1908). - Pototsky, Viacheslav (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Goal. The purpose of the article is to consider the peculiarities of the activities of Protestant sects (primarily Baptists) on the territory of the Kharkiv province at the beginning of the 20th century. The chronological boundaries of this study cover the period from 1905 to 1908. This is the period between the proclamation of freedom of conscience in the Russian Empire and the beginning of the reactionary policy of the tsarist government and its law enforcement agencies.Research methodology. The methodological basis of the article consists of the principles of historicism and objectivity, implemented using a number of methods: general logic (analysis and synthesis), as well as classification, comparative and periodization methods.Scientific novelty. The subject of a special scientific study was the organizational and propaganda work of religious dissidents in conditions of relative tolerance and lack of pressure from the state and the official church.Conclusions. Imperial manifestos of 1905 and 1906. on freedom of conscience and religion completely changed the lives of the sectarians of the Kharkiv province. It was established that in the period from 1905 to 1909 in the province, dissidents were not hindered by either the police or the Russian Orthodox Church. The latter was in a kind of embarrassment from the great freedoms that were granted to the sectarians. In addition, the dissidents themselves everywhere violated the provisions of the manifesto on the prohibition of propaganda and actively called on the Orthodox to join the sect. The period 1905–1909 can be called a time of experimentation, when both sectarians and representatives of the authorities and the Russian Orthodox Church had to try to coexist under conditions of mutual compromise. After many decades of open confrontation, such processes encountered many difficulties in local conditions.